Comparison of Single versus Double Lateral Plating in Treatment of Feline Ilial Fractures Using Veterinary Cuttable Plates - Wiersema, Tijn; Koolen, Ties; Theyse, Lars F. H.; Maarschalkweerd, Roelof J.; van Zuilen, Cornelis D.; van Rijn, Sarah J. (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to compare the frequency of implant failure and the extent of pelvic canal narrowing associated with the fixation of ilial fractures in cats with a single veterinary cuttable plate (SLP) or double veterinary cuttable plates (DLP) applied to the lateral surface of the ilium.Study Design Radiographic evaluation of feline ilial fractures plated laterally using SLP or DLP. Pelvic canal narrowing directly postoperatively and at 6 weeks follow-up was objectively measured using the sacral index (SI). Radiographs were evaluated for implant failure and fracture healing.Results Seventy-seven cats satisfied the inclusion criteria. Twenty-nine fractures were treated with a SLP and 48 with DLP. Implant failure occurred significantly more (p = 0.001) in the SLP group (14/29) compared with the DLP group (6/48). Follow-up SI was significantly different between the two groups (p = 0.048, SLP median: 1.0 range: 0.83–2.4, DLP median: 0.98; range: 0.76–1.45). Median change in SI was −0.04 (range: −1.4 to 0.05) in the SLP group and 0.0 (range: −0.23 to 0.23) in the DLP group. This difference was significantly different (p = 0.031).Conclusion DLP leads to significantly less implant failure and significantly less pelvic canal narrowing compared with SLP. This difference in pelvic canal narrowing was small and the clinical relevance remains unclear.
Keywords: feline; veterinary cuttable plate; implant; double plating; ilial fracture